Snare drum player at candlelight vigil - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a snare drum player participating in the candlelight vigil to San Francisco City Hall in memory of San Francisco mayor, George Moscone, and San Francisco supervisor, Harvey Milk, who had been assasinated by Dan White. Around him are others marching with candles and flags.